Diurnal and seasonal course of monoterpene emissions from Quercus ilex(L.) under natural conditions application of light and temperature algorithms - Bertin, N; Staudt, M; Hansen, U; Seufert, G; Foster, P; Fugit, J L; Torres, L (Atmospheric Environment, 1997)
Quercus ilex is a common oak species in the Mediterranean vegetation and a strong emitter of monoterpenes. Since the short-term control of monoterpene emissions from this species involved both temperature and light, the usual exponential function of temperature may not be sufficient to model the diurnal and seasonal emission course. In the frame of the BEMA-project (Biogenic Emissions in the Mediterranean Area), we investigated the tree-to-tree, branch-to-branch, diurnal, and seasonal variability of monoterpene emissions from Q. ibex over one and a half years at Castelporziano (Rome, Italy). In addition, w,: checked the suitability of the model developed for isoprene by Guenther et al. (1991, 1993) to simulate the short- and long-term variations of monoterpene emissions from this particular species. We found that the tree-to-tree variability was rather small compared to the experimental error during air sampling and analysis by diverse laboratories. The branch-to-branch variability was noticeable between sun- and shade-adapted branches only. 80% of total emissions were represented by cc-pinene, B-pinene and sabinene, whose proportions were stable over the year and independent of light exposure. The emission factor (emission rate at 30°C and 1000 ~molphotonm-Zs-l ) estimated by the isoprene model or extrapo- lated from measurements was similar: it was about 22 pggdw -r h-r for sun-exposed branches and 2.3 pggdw.-’ h-r for shade-adapted branches. It was rather stable over the seasons except during leaf development. The diurnal and seasonal emission patterns from Q. ibex were simulated in a satisfying way by Guenther’s algorithms especially if we excluded the laboratory variability. For shade-adapted branches, an emission factor 17 times lower had to be applied, but temperature and light responses were unchanged.
Keywords: Holm oak; index; light and temperature algorithm; Mediterranean vegetation; Modelling; Monoterpene; Quercus ilex

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E - Kesselmeier, J; Fer, L S C H; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Foster, I P; Jacob, V; Denis, J; Fugit, J L; Dutaur, L; Torres, L; et al. (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.
Keywords: Biogenic emission; isoprene; light; Monoterpenes; non-methane hydrocarbons; oak; Plant physiology; VOC